FILSAFAT BARAT ERA SKOLASTIK (Telaah Kritis Pemikiran Thomas Aquinas) - Muhammad Taufik (Jurnal Ilmiah Ilmu Ushuluddin, 2020)
This paper tries to discuss how Western philosophy critically examined the thought of Thomas Aquinas in the scholastic era. The scholastic era or known medieval philosophy whose style is the philosophy of collaborating with theology in harmony. Philosophy in the scholastic era gave birth to many famous theologians-philosophers, one of whom was Thomas Aquinas, who was the subject of this paper. After the authors traced through this paper the answer found that Aquinas was the most important figure of Western philosophy in the scholastic era. Aquinas is considered to have made a real contribution in unifying the original elements of Augustine's thought, strongly influenced by the philosophy of Neo-Platonism, with the philosophy of Aristotle. The author criticized Aquinas's view that Aristotle's philosophical system contains true rational truths. Basically using philosophical methods to understand theology is very helpful. That has been done by Aquinas; it only needs to be underlined that the method for understanding philosophy without losing the nature of theology is not entirely correct either. However there are also problems that cannot be fully explained by philosophical approaches. Like the problem of beliefs related to metaphysical problems, for example. The problem of belief in matters that are metaphysical is a problem that is difficult to explain philosophical logic. Aquinas stated that theological truth is clear to human reason. For example, it is the truth about God's existence. This truth comes from revelation, but how to explain philosophically that can satisfy curiosity so that what is believed can be understood rationally.